The presence of HPV DNA in cervical cancer: Correlation with clinico-pathologic parameters and prognostic significance: 10 years experience at the Department of Obstetrics and Gynecology of the Mainz University. Issue 1 (1st January 2001) - Pilch, H.; Günzel, S.; Schäffer, U.; Tanner, B.; Brockerhoff, P.; Maeurer, M.; Höckel, M.; Hommel, G.; Knapstein, P. G.
Abstract : The objective of this study was to assess whether the presence of human papillomavirus (HPV) DNA and/or several genotypes of HPV DNA in cervical cancer are correlated with several clinicopathologic parameters of well-defined prognostic significance and whether virologic parameters are predictors of long-term survival in cancer patients. Two hundred twenty three cases of cervical cancer patients included in this retrospective study underwent follow-up evaluation. Survival and cause of death were examined for 204 (91.4%) patients, with a mean follow-up time of 4.4 years. HPV DNA was detected using the highly sensitive polymerase chain reaction (PCR) method followed by HPV DNA sequencing for HPV genotyping. These results were correlated with well-defined clinicopathologic parameters and survival data. HPV DNA was detected by PCR in 150 of 193 (73.4%) tissue specimens of cervical cancer patients. DNA sequence analysis revealed the presence of HPV 16 ( n = 68, 45.3%), HPV 18 ( n = 49, 32.6%) and rare HPV types ( n = 33, 22.1%). HPV genotypes correlated significantly with histologic tumor types, node status, tumor oxygenation, blood vessel invasion, and lymph space involvement. The presence of HPV DNA in cervical cancer as well as the genotype of HPV 16 could also be confirmed as significant prognostic factors in the univariate Cox regression analysis (RR 2.856, P < 0.003 resp. RR 3.444, P < 0.0001). In the multivariate analysis, however, HPV DNA status failed to be of prognostic relevance. Exclusively HPV 16 appears to have an independent impact on the overall survival in cervical patients (RR 3.653, P < 0.002). We conclude that the detection of HPV 16 genotype may play an important adjunct role in assessing prognosis of cervical cancer patients. The clinical impact of the presence of HPV DNA in primary tumors of uterine cervix remains to be investigated in further studies, and the exact mechanisms by which HPV influences the prognosis of cervical cancer patients have to be defined.